1998
DOI: 10.1073/pnas.95.18.10407
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease A variants with potent cytotoxic activity

Abstract: Select members of the bovine pancreatic ribonuclease A (RNase A) superfamily are potent cytotoxins. These cytotoxic ribonucleases enter the cytosol, where they degrade cellular RNA and cause cell death. Ribonuclease inhibitor (RI), a cytosolic protein, binds to members of the RNase A superfamily with inhibition constants that span 10 orders of magnitude. Here, we show that the affinity of a ribonuclease for RI plays an integral role in defining the potency of a cytotoxic ribonuclease. RNase A is not cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
304
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(317 citation statements)
references
References 56 publications
11
304
2
Order By: Relevance
“…21,20 In the crystalline hRI路RNase 1 complex, the 尾4-尾5 loop adopts a similar conformation to that of RNase A in the pRI路RNase A complex ( Figure 3). One major difference is with residue 88, as Asn88 of RNase 1 forms a hydrogen bond with Glu264 instead of residing in the pocket formed by Trp261 and Trp263.…”
Section: Recognition Of Rnase 1 By Rimentioning
confidence: 99%
See 1 more Smart Citation
“…21,20 In the crystalline hRI路RNase 1 complex, the 尾4-尾5 loop adopts a similar conformation to that of RNase A in the pRI路RNase A complex ( Figure 3). One major difference is with residue 88, as Asn88 of RNase 1 forms a hydrogen bond with Glu264 instead of residing in the pocket formed by Trp261 and Trp263.…”
Section: Recognition Of Rnase 1 By Rimentioning
confidence: 99%
“…Previous studies of the RI路ribonuclease interface have focused on short-range intermolecular contacts between the proteins, thereby raising the dissociation rate. 21,22,17 Diminishing the affinity of RNase 1, the human homologue of RNase A, by modulating short-range interactions has, however, proven to be difficult. 23-25 Although RNase 1 and RNase A share 70% sequence identity, mutagenesis studies have indicated substantial variation in how each is recognized by RI.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the role of RI in the cell is that of a ''sentry'', to protect its cytosolic RNA from extracellular RNases that may enter that compartment [5]. This hypothesis is based on the following evidence: RI resistant RNases, such as bovine seminal RNase [6] and onconase [7], are cytotoxic; noncytotoxic RNases, strongly inhibited by RI, become cytotoxic when they are engineered into relatively RI-resistant RNases [8]; cells manipulated to increase the RI levels become more resistant to RNase cytotoxicity [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This unusual biological activity is critically dependent on the ribonucleolytic activity 8 and on the ability of these molecules to reach the cellular cytosol and to degrade RNA by evading the action of the ribonuclease inhibitor (RI). 9,10 It is currently accepted that RI, which binds most RNase A family members with femtomolar affinities, plays an important role in the protection of host cells from endogenous RNases. [9][10][11] Only frog RNases such as Onconase TM (ONC) 12 and BSRNase [13][14][15] are resistant to human RI.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is currently accepted that RI, which binds most RNase A family members with femtomolar affinities, plays an important role in the protection of host cells from endogenous RNases. [9][10][11] Only frog RNases such as Onconase TM (ONC) 12 and BSRNase [13][14][15] are resistant to human RI. The former, which is in Phase III clinical trials as an antitumor agent against malignant mesothelioma, 3 escapes RI because it lacks many of the residues involved in the RNase A-RI recognition.…”
Section: Introductionmentioning
confidence: 99%